Hubungan Kebiasaan Makan dan Aktivitas Fisik Dengan Status Gizi Pada Remaja Tahun 2024 - Jumia Riska Putri Aji Utami; Nurul Ainul Shifa; Nining Rukiah (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Adolescence really requires higher levels of nutrition because of the physical growth and development that occurs from childhood to adolescence. Deviant eating habits certainly have an impact on nutritional problems such as undernutrition or overnutrition. The aim of this research is to determine the relationship between eating habits and physical activity and the nutritional status of adolescents in 2024. This research uses quantitative methods with a cross sectional design with 105 students at Al-Falah Islamic Middle School and uses random sampling techniques. This research instrument used the AFHC (Adolescent Food Habits Checklist) questionnaire and the GPAQ (Global Physical Activity Questionnaire). The chi square results obtained for the relationship between eating habits and adolescent nutritional status were p-value, namely 0.00 <0.05 and the chi square results for the relationship between physical activity and adolescent nutritional status were p-value, namely 0.00 <0.05, so there was a relationship between Physical Activity and Adolescent Nutritional Status.